1981
DOI: 10.1080/00268978100102351
|View full text |Cite
|
Sign up to set email alerts
|

Noble gas molecular ions

Abstract: Self-consistent field calculations are reported for a number of diatomic and polyatomic ions containing helium. The stability and the nature of the bonding in these molecular ions is examined. The possibility of observing noble gas molecular ions in laboratory experiments and in the interstellar medium is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0
1

Year Published

1987
1987
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 16 publications
0
13
0
1
Order By: Relevance
“…The SCF potential energy curve (PEC) for the ground state 3 AE À was found to enjoy a (global) minimum at R e ¼ 1:34 Å [17] or around R e % 1:2 Å [18]. Its failure to converge to the proper separated-atoms limit, however, led to the incorrect conclusion that HeO 2þ should be a thermochemically stable species.…”
Section: Metastability Of Heo 21mentioning
confidence: 87%
See 2 more Smart Citations
“…The SCF potential energy curve (PEC) for the ground state 3 AE À was found to enjoy a (global) minimum at R e ¼ 1:34 Å [17] or around R e % 1:2 Å [18]. Its failure to converge to the proper separated-atoms limit, however, led to the incorrect conclusion that HeO 2þ should be a thermochemically stable species.…”
Section: Metastability Of Heo 21mentioning
confidence: 87%
“…In early SCF studies of HeO 2þ , small basis sets with Slater functions were invoked to compute energies for the electronic ground state 3 AE À [17,18] and for some low-lying excited states [17]. The SCF potential energy curve (PEC) for the ground state 3 AE À was found to enjoy a (global) minimum at R e ¼ 1:34 Å [17] or around R e % 1:2 Å [18].…”
Section: Metastability Of Heo 21mentioning
confidence: 99%
See 1 more Smart Citation
“…Although the HeCN + ion has not been found in space, it has nevertheless emerged from subsequent studies that simple ions containing helium have a rich chemistry (see, for example, the recent review by Grandinetti [13]). The structure and stability of helium-containing polyatomic cations have been investigated by a number of authors [12,[14][15][16][17][18][19][20]. In a paper published in 1999, Olah et al [19] found the helionitronium trication, HeNO 3+ 2 , to be unusually stable.…”
mentioning
confidence: 99%
“…There have been a number of studies (1)(2)(3)(4)(5)(6)(7) that have examined the stability of such cations. The studies of Koch and Frenking (4), Schleyer (5), and Wong et al (6) all have shown that polyatomic cations are capable of forming strong bonds with helium.…”
mentioning
confidence: 99%